On the "Preconditioning" Function Used in Planewave DFT Calculations and its Generalization. (3rd July 2015) - Zhou, Yunkai; Chelikowsky, James R.; Gao, Xingyu; Zhou, Aihui
Abstract The Teter, Payne, and Allan "preconditioning" function plays a significant role in planewave DFT calculations. This function is often called the TPA preconditioner. We present a detailed study of this "preconditioning" function. We develop a general formula that can readily generate a class of "preconditioning" functions. These functions have higher order approximation accuracy and fulfill the two essential "preconditioning" purposes as required in planewave DFT calculations. Our general class of functions are expected to have applications in other areas.